Solid carbon-assisted steam electrolysis in solid electrolyte cells for energy storage - Bamburov, Aleksandr (2024)
The development of solid oxide electrolysis cell (SOEC) technology for generation of green hydrogen using renewable electricity faces challenges due to high-temperature degradation processes, particularly those occurring at the anode/electrolyte interface. Using solid carbon as a depolarizing agent at the anode is an innovative concept enabling the reduction of oxygen chemical potential at the anode/electrolyte interface, thereby eliminating the risks of high oxygen pressures and related degradation factors. This works aimed to explore the concept of carbon assisted electrolysis cell (CA-SOEC) and the materials that could be employed in this type of electrochemical system. The research was focused on the design, fabrication, and detailed characterization of the components for CA-SOEC cells, including the development of an alternative diffusion barrier layer material for operation under reducing conditions (Chapter 3), optimization of the protocol for fabricating Ni/YSZ cathodes (Chapter 4), evaluation of SrFe0.75Mo0.25O3-δ (Chapter 5) and Sr0.85Pr0.15TiO3+δ (Chapter 6) as potential anode materials, and preliminary electrochemical tests of model CA- SOECs (Chapter 7). Pyrochlore-type (Y0.9Ca0.1)2Ti2O7-δ is demonstrated to be a promising candidate for the diffusion barrier layer. This material is a nearly pure ionic conductor in a wide range of p(O2)-T conditions, exhibits acceptable electrical conductivity (4.3×10-2 S/cm at 900°C in air), moderate thermal expansion (TEC = 10.3×10-6 K-1), negligible chemical expansion, and chemically compatible with YSZ electrolyte and SrFe0.75Mo0.25O3-δ electrode. Perovskite-like SrFe0.75Mo0.25O3-δ and Sr0.85Pr0.15TiO3+δ exhibit similar levels of n- type electronic conductivity under reducing conditions. While SrFe0.75Mo0.25O3-δ ceramics show excessive thermochemical expansion at elevated temperature compromising the thermomechanical stability of electrode/electrolyte assembly during p(O2)-T cycling, donor-doped strontium titanates benefit from suitable thermal and insignificant chemical expansion under similar conditions. Although both materials showed moderate electrochemical performance in a diluted hydrogen atmosphere under OCV conditions at 800-850°C, the performed experiments revealed the prospects for their further optimization. Preliminary tests of model CA-SOECs based on electrolyte-supported YSZ cells with Ni/YSZ anode, SrFe0.75Mo0.25O3-δ cathode, CGO or (Y0.9Ca0.1)2Ti2O7-δ diffusion barrier interlayers at the anode side, and anode chamber filled with solid carbon, showed a decrease in OCV to ~0 V at 850°C, confirmed the functionality of the concept, and identified the approaches for future research and experimental optimization